NILAI-NILAI PENDIDIKAN TAUHID PERSPEKTIF SYEKH AHMAD AL-MARZUKI DALAM KITAB AQIDATUL AWAM - Sari, Susi Siviana; Alfatah, Akhid Ilyas (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2021)
This research focuses on the Values of Tawhid Education. This study aims to find out how the education of monotheism according to Sayid Ahmad Al-Marzuki in the Aqidatul Awam book. Tawhid is the essential teaching because it contains instructions about the recognition of the oneness of Allah SWT as a consequence and pure existence and is a foundation and principle as a place for all deeds, and in essence, is to form a monotheistic human being. This research is library research, which focuses on discussing literature related to the focus of research, such as books that can be used as a reference source. In the results of this study, researchers found the value of monotheism education in Sheikh Ahmad Al-Marzuki that faith education consists of faith in Allah, Angels, books, Apostles, the last day, and qadha and qadar. The value of monotheism education is also closely related to Allah SWT, oneself, and fellow human beings.